2011
DOI: 10.3832/ifor0563-004
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Cadmium distribution in roots of Salicaceae through scanning electron microscopy with x-ray microanalysis

Abstract: A screening in hydroponics was carried out to assess the potential of Cd uptake and metal accumulation in roots of 4 poplar and 2 willow clones. Rooted cuttings were exposed for 3 weeks to 50 μM Cd sulphate in a growth chamber. Salicaceae clones were discriminated in their potential to absorb and distribute Cd in root tissues considering the interaction between metal and macronutrients. SEM-EDXMA was useful to investigate structural modifications and to identify in situ concentration and distribution of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Contradictory results regarding the influence of Cd in shoot micronutrient concentrations have been published (Yang et al 1996, Larbi et al 2002, Dong et al 2006, Lopez-Millan et al 2009 underlying differences among species as well as the dependence on metal concentrations. In an experimental screening of metal accumulation in roots of four poplar (including I-214) and two willow clones, Cocozza et al (2011) found a positive relationship between Cd and Ca contents in roots suggesting that the accumulation of Cd did not interfere with Ca absorption. Cd may affect water and ion channels and transport of osmotically active compounds (Perfus-Barbeoch et al 2002) and so development of water stress.…”
Section: Discussionmentioning
confidence: 98%
“…Contradictory results regarding the influence of Cd in shoot micronutrient concentrations have been published (Yang et al 1996, Larbi et al 2002, Dong et al 2006, Lopez-Millan et al 2009 underlying differences among species as well as the dependence on metal concentrations. In an experimental screening of metal accumulation in roots of four poplar (including I-214) and two willow clones, Cocozza et al (2011) found a positive relationship between Cd and Ca contents in roots suggesting that the accumulation of Cd did not interfere with Ca absorption. Cd may affect water and ion channels and transport of osmotically active compounds (Perfus-Barbeoch et al 2002) and so development of water stress.…”
Section: Discussionmentioning
confidence: 98%
“…However, compared with other ions, the distribution of Cd within the root was preferentially localised in the surroundings of central cylinder. In other experiments with the same Cd concentrations (50 μM) but different poplar genotypes (A4A and I-214 Populus x canadensis Mönch., Poli and 58-861 Populus nigra L.), the same authors (Cocozza et al 2011) showed that I-214 plants were characterised by high Cd contents in the epidermis, whereas 58-861, A4A, and Poli showed high Cd contents in the cortex.…”
Section: Anatomical and Morphological Modificationsmentioning
confidence: 91%
“…Tuttavia, le piante esposte ad alte concentrazioni di Cd possono mostrare effetti di tossicità, come clorosi fogliare, inibizione della crescita, riduzione dell'assorbimento d'acqua e di nutrienti, alterazione dell'attività enzimatica, limitazione degli scambi gassosi, senza per questo limitare l'assorbimento del metallo nei vari compartimenti della pianta (Sanità di Toppi & Gabbrielli 1999, Pietrini et al 2003, Cocozza et al 2008, Zacchini et al 2009, Cocozza et al 2011. L'obiettivo del presente studio è stato di valutare la risposta di semenzali di roverella (Quercus pubescens Willd.…”
Section: Abstract: Ecophysiological Characteristics and Cadmium Accumunclassified